2020
DOI: 10.1021/acsami.0c08440
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Nitrogen-Heteroatom Configuration for Enhanced Charge-Storage Performance and Reliability of Nanoporous Carbon Electrodes

Abstract: In this study, various nitrogen-containing functional groups, namely, pyridine (N-6), pyrrole (N-5), oxidized N (N–O), and quaternary N (N-Q), are created on activated carbon (AC) surface via melamine, ammonia, and nitric oxide doping methods. N-5 and N-6 groups markedly alter the specific surface area and pore size of AC. N–O is found to affect electrolyte wettability, and the N-Q content is closely associated with AC electronic conductivity. The nitrogen-containing groups do not contribute to pseudocapacitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Sutarsis and coworkers treated commercial activated carbon with melamine, ammonia gas/argon and nitric oxide (NO) to finely tune the content of N-containing functional groups of activated carbon [70]. Subsequently, the leakage current for supercapacitor electrodes with different N-containing levels was evaluated in the propylene carbonate electrolyte.…”
Section: Activated Carbonmentioning
confidence: 99%
“…Sutarsis and coworkers treated commercial activated carbon with melamine, ammonia gas/argon and nitric oxide (NO) to finely tune the content of N-containing functional groups of activated carbon [70]. Subsequently, the leakage current for supercapacitor electrodes with different N-containing levels was evaluated in the propylene carbonate electrolyte.…”
Section: Activated Carbonmentioning
confidence: 99%
“…Recently, another research group also reported that the surface modification with NO is effective for the improvement of the durability and the rate performance. 42 The electrochemical stability is the key to finding the effective surface modification for the improvement of the operating voltage of the nanoporous carbon electrode.…”
Section: Nitrogen-dopingmentioning
confidence: 99%
“…The evolved gas can block the pores of the electrode material and separator and thus increase the capacitor internal resistance and pressure, leading to performance degradation, cell rupture, and even safety risks. [10,11] The self-discharge rate of SCs should also be considered. Self-discharge, which involves voltage depression when SCs are disconnected from a power supply, can result in coulombic efficiency loss and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Moreover, the aging behavior at high voltage is of a great concern because long-term durability is an essential characteristic of SCs. [11] However, due to the emphasis (sometimes overemphasis) on high capacitance, few studies have focused on improving these crucial properties of carbon-based EDLCs. These properties are thus investigated in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation